Didactic Strategy Mediated by the Game, to Minimize Learning Difficulties in Students (2023)
The Covid-19 virus pandemic generated various problems in educational training centers worldwide; Colombia has not been the exception. One of these most evident problems is the low academic performance that students have had in recent years, not to mention the high increase in teaching and learning process difficulties; difficulties such as low instructional follow-up, little assertive communication, scattered attention, and the lack of age-appropriate socio-emotional skills. Having said that, a qualitative research methodology is proposed here from the IA design, carried out República de Colombia, IED School, more specifically in branch B. The objective of minimizing learning difficulties through a didactic strategy based on games, which enables the reduction of learning difficulties in course 104 students’ course 104.The idea is to enhance learning through computational thinking while taking part in games as a transversal axis. Regarding the planning, implementation and evaluation, teachers of the course will be directors-researchers and students and parents are also actively integrated into the project, with participation, dedication, and commitment in the development of the implementation and evaluation of the didactic strategy. The idea is to check information and situation about: significant reduction in loss of the academic year in children with learning difficulties, associated work between the institution and families, positive effect of the game in most learning environments, promoting computational thinking (PC) within the cognitive abilities and problem-solving context. Finally, it is concluded that the strategy was well received by the educational community, due to the great impact on the integral training processes of the participants and at the same time the methodological strategy was accepted, in the planning of the year 2023 in the first grade.